Financial Development in Latin America and the Caribbean : Stylized Facts and the Road Ahead - Didier, Tatiana; Schmukler, Sergio L. (World Bank, Washington, DC, 2013)
The paper documents the major trends in financial development in Latin America and the Caribbean since the early 1990s. The paper compares trends in Latin America and the Caribbean with those in Asia, Eastern Europe, and advanced countries and compares countries within Latin America and the Caribbean. The findings show that financial systems in the Latin America and the Caribbean region have become more diversified and more complex. In particular, domestic financial systems have become less bank-based, with bond and stock markets playing a larger role; institutional investors have gained some space in channeling domestic savings, thus increasing the availability of funds for investment in capital markets; and several economies in the region have started to reduce currency and maturity mismatches. Nonetheless, a few large companies continue to capture most of the domestic savings. And because these trends have unfolded more slowly than pro-market reformers had envisioned, broad, market-based financial systems with dispersed ownership have yet to materialize fully in the region. As a result, convergence is still largely failing to happen and the region's financial systems remain less developed than those of the advanced economies and several other emerging economies, most notably those in Asia.